Distributed lags : problems of estimation and formulation - Dhrymes, Phoebus J. (Amsterdam ; New York : North-Holland Pub. Co. : sole distributors for the U.S.A. and Canada, Elsevier North-Holland, 1981)
The book deals primarily with problems of estimation in the context of distributed lag models of various orders of complexity and only peripherally with the theoretical bases in the formulation of such models. The book is addressed to both the graduate student of econometrics and the specialists
Includes index.
Bibliography: p. 458-466.
rpm 18/09/2017
Loans
Keywords: Distributed lags (Economics); Econometrics